Highway planning, survey, and design - Al-Khateeb, Ghazi Gaseem (Boca Raton, FL : CRC Press, 2021)
Highway Planning, Survey, and Design presents the latest engineering concepts, techniques, practices, principles, standard procedures, and models that are applied and used to design and evaluate alternatives of transportation systems and roadway horizontal and vertical alignments and to forecast travel demand using variety of trip forecasting models to ultimately achieve greater safety, sustainability, efficiency, and cost-effectiveness. It provides in-depth coverage of the major areas of transportation engineering and includes a broad range of practical problems and solutions, related to theory, concepts, practice, and applications. Solutions for each problem follow step-by-step procedures that include the theory and the derivation of the formulas and computations where applicable. Additionally, numerical methods, linear algebraic methods, and least squares regression techniques are presented to assist in problem solving. Features: Presents coverage of major areas in transportation engineering: urban transportation planning, highway surveying, and geometric design of highways. Provides solutions to numerous practical problems in transportation engineering including terminology, theory, practice, computation, and design. Offers downloadable and user-friendly MS Excel spreadsheets as well as numerical methods and optimization tools and techniques. Includes several practical case studies throughout. Implements a unique approach in presenting the different topics. Highway Planning, Survey, and Design will help academics and professionals alike to find practical solutions across the broad spectrum of transportation engineering issues.
OCLC-licensed vendor bibliographic record.
Keywords: Highway planning; Highway engineering